Failure pattern and radiotherapy exploration in malignant pleural effusion non-small cell lung cancer treated with targeted therapy - Li, Qingsong; Hu, Cheng; Su, Shengfa; Ma, Zhu; Geng, Yichao; Hu, Yinxiang; Li, Huiqin; Lu, Bing (Frontiers in Oncology, 2023)
Purpose—Actionable mutations are common in non-small cell lung cancer（NSCLC）with malignant pleural effusion（MPE）(MPE-NSCLC). The pattern of failure in MPE-NSCLC treated with targeted therapy after MPE control remains unclear. We aimed to investigate the failure pattern of such patients in a cohort study and explore the possibility of radiotherapy. Patients and methods— Computed tomography scans of 86 patients were reviewed in this study. We classified first pattern of failure after MPE control as initial disease sites only (IF), new distant sites only (NF), or IF and NF detected simultaneously (INF). Patients evaluated suitable for radiotherapy after disease progression were divided into two groups：D group without radiotherapy and RD group with radiotherapy. The Kaplan-Meier method and log-rank test were used for survival analyses. Results—Disease progression after MPE control was observed in 42 patients with complete serial imaging. Median time to any progression was 9.5 months. Rate of the IF, NF and INF were 50%, 17% and 33% for all patients ,60%,0% and 40% for patients with MPE recurrence (n=10,23.8%) and 47%, 22% and 31% for patients (n=32,76.2%) without MPE recurrence, respectively. Out of 10 patients(23.8%) with MPE recurrence，7 patients simultaneous underwent primary tumor progression and 5 MPE were cytologically confirmed in 7 patients with examination. The overall survival （OS ）rates at 1, 2, 3 years for the RD group and D group were 88.2%, 50.5%, 21.7% and 80.0%, 20.3%, 0%, respectively; the corresponding MST were 26.1 months and 17.5 months, respectively (χ2=4.959, p =0.026) Conclusions—Our data indicates that 50% of patients with actionable mutations MPE- NSCLC after MPE control are likely to fail at their initial sites of disease and the use of radiotherapy may bring OS benefits during the course of their disease. Multicenter RCT is necessary to confirm the result in the future.